Phonotactics in the Syllables of Batak Toba Dialect - Jamorlan Siahaan; Asni Barus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The title of this journal was “Phonotactics in the Syllables of Batak Toba dialect” which studied syllables, vocal row and consonant row. The background of this study was by imitating one’s utterance in a written form and pronunciation in basic words. The objective was to determine the syllable structure, vowel row, and consonant row. Its benefit was that it could be used as teaching materials at senior high schools and colleges, esppecially in of Bataknese literature study program. It could also be used as the contribution to the development of the National Literature. The research used linguistic descriptive theory, library research, observton, and   interviews. The result of the research showed that there were 7 (seven) types of syllable in the Batak Toba dialect: 1) word which consisted of one syllable, 2) word which consisted of two syllables, 3) word which consisted of three syllables, 4) word which consisted of four syllables, 5) word which consisted of five syllables, 6) word which consisted of six syllables, and 7) word which consisted of sseven syllables. Nucleus (a, i, u, e, o), Onset (b, d, j, g, p, t, k, m, n, h, s, h, l, r), Code (p, t, k, m, n, h, s, l, r). Syllables based on vowel row were /-ao-/ and /-uae-/ and consonant row were /-rs-/ and /-nd-/.